The Relationship Between Hypertension and Uric Acid Levels Among Police Officers Aged 30–60 Years at the Pasuruan Police Resort - Kusumaningtyas, Nisa Priamita; Sunaryati, Titiek; Sugeng, Maria Widjianti (Sean Institute, 2025)
Hypertension and hyperuricemia are two metabolic conditions that frequently coexist and may lead to cardiovascular complications. This study was motivated by the high prevalence of hypertension and elevated uric acid levels among individuals in their productive age, particularly in high-stress occupations such as police officers. The aim of this research was to determine the relationship between hypertension and uric acid levels among police officers aged 30–60 years at the Pasuruan Police Department. This quantitative research used a cross-sectional design with an analytic approach. A purposive sampling technique was employed to select 60 respondents, and data were collected through blood pressure and uric acid level examinations. Data were analyzed using the Chi-Square test. Results showed that 83.3% of respondents had hypertension and 28.3% had hyperuricemia. The Chi-Square test indicated a significant relationship between hypertension and uric acid levels (p = 0.005). It can be concluded that there is a relationship between hypertension and uric acid levels, where individuals with hypertension are more likely to experience hyperuricemia. It is recommended that regular monitoring of blood pressure and uric acid levels be conducted among individuals in their productive age, along with the adoption of a healthy lifestyle as a promotive and preventive measure against further complications.